Performing Memoria: A Theatre Performance Giving Voice to Speechless Memories - Kuhlmann, Annelis (Nordic Theatre Studies, 2019)
Odin Teatret’s Memoria (1990) centres round an actor’s conflict with the act of remembering. In this article, however, one strand follows Giorgio Agamben’s presentation of “remnants of Auschwitz”, which is based on the story of Hasidic children’s experience of surviving World War II, and how for some survivors, the guilt of surviving while others perished is too great a burden to bear, so much so that suicide seems their only route to peace. A further strand builds on Rebecca Schneider’s ideas about the very act of re-enacting remembrance as a performance, which remains once all living memories of historical facts are gone. On a more specific level, Memoria brings together the narrative of the Hasidic Tales of the Holocaust (1983) with memories from philosophers such as Primo Levi and Jean Améry, with Else Marie Laukvik and Frans Winther giving voice to these speechless memories. Laukvik, who is the author of the Memoria script, also manages to embody the conflict that can arise from remembering in her performance. The article is based on watching Memoria, as well as archive materials, personal interviews, and other performances by Else Marie Laukvik, who is also the author of the Memoria script.